Malaysia my second home: The influence of push and pull motivations on satisfaction - Wong, Brian Kee Mun; Musa, Ghazali; Taha, Azni Zarina (Elsevier, 2017)
Malaysia's second home retirement tourism programme attracted participants globally and reached its peak in 2013. The numbers started to dwindle in 2014, particularly among the once-top nationalities: the British, Japanese, and Iranians. The lack of data on the participants' motives and satisfaction levels in quantitative forms justifies the need for this study. This research examines the ‘Malaysia My Second Home’ (MM2H) participants' motivation, satisfaction, and the relationship between the two constructs. Of the 504 usable samples, we used 280 for scale development and 224 for the structural model assessment. The empirical analyses validated the conceptual model. The results revealed four ‘push’ and seven ‘pull’ motivation factors respectively. Push motivations (β = 0.568) displayed a stronger influence on the participants' overall satisfaction. The findings suggest the need for human centric marketing strategies and improvement in the central government management to enhance the attractiveness of the MM2H programme for international retirees.